2022
DOI: 10.1001/jamainternmed.2021.7171
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Clinical Evidence Supporting Repository Corticotropin Injection for FDA-Approved Indications

Abstract: IMPORTANCE Repository corticotropin injection is an expensive medication that was approved in 1952 for the treatment of many inflammatory conditions. The clinical evidence supporting the use of repository corticotropin (hereinafter referred to as corticotropin) has been weak, perhaps because its approval predated the modern review standards of the US Food and Drug Administration (FDA).OBJECTIVE To characterize the clinical evidence supporting the use of corticotropin for its FDA-approved indications.EVIDENCE R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Unfortunately, data regarding the primary indications of ACTH in medicine remain inconclusive. According to a very recent scoping review [94], most randomized controlled trials have not found any significant clinical benefit of many ACTH indications that are FDA approved over oral CS. But in several trials analyzed above, ACTH has been proven truly beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, data regarding the primary indications of ACTH in medicine remain inconclusive. According to a very recent scoping review [94], most randomized controlled trials have not found any significant clinical benefit of many ACTH indications that are FDA approved over oral CS. But in several trials analyzed above, ACTH has been proven truly beneficial.…”
Section: Discussionmentioning
confidence: 99%